Male terminalia morphology of sixteen species of the Drosophila saltans group Sturtevant (Diptera, Drosophilidae) - Roman, Bruna Emilia; Madi-Ravazzi, Lilian (Zootaxa, 2021)
Male terminalia in insects with internal fertilization evolve more rapidly than other structures. The aedeagus is the most variable structure, making it a valuable diagnostic feature to distinguish species. The saltans group Sturtevant of Drosophila Fallén contains sibling species, that can be distinguished by their aedeagi. Here, we revised and illustrated the morphology of the male terminalia of the following species: Drosophila prosaltans Duda, 1927; D. saltans Sturtevant, 1916; D. lusaltans Magalhães, 1962; D. austrosaltans Spassky, 1957; D. septentriosaltans Magalhães, 1962; D. nigrosaltans Magalhães, 1962; D. pseudosaltans Magalhães, 1956; D. sturtevanti Duda, 1927; D. lehrmanae Madi-Ravazzi et al., 2021; D. dacunhai Mourão & Bicudo, 1967; D. milleri Magalhães, 1962; D. parasaltans Magalhães, 1956; D. emarginata Sturtevant, 1942; D. neoelliptica Pavan & Magalhães in Pavan, 1950; D. neosaltans Pavan & Magalhães in Pavan, 1950 and D. neocordata Magalhães, 1956. We found that phallic structures (e.g., the aedeagus) evolve more rapidly than periphallic structures (e.g., epandrium), being completely different among the subgroups and within them. This rapid evolution may be due to the action of sexual selection or to the potential role of those structures in speciation.